Evaluation of the presence of gluten in oat flour labeled "gluten free" sold in Brazil. - Sganzerla, Amanda; Sganzerla, Alice; Vargas, Fabiana Magnabosco de; Silvestre, Wendel; Baldasso, Camila (Nutrivisa Revista de Nutrição e Vigilância em Saúde, 2025)
Gluten is a protein found in grains such as wheat, rye, and barley, and also in oats when cross-contaminated. While safe for most people, gluten can cause serious health issues in individuals with celiac disease, non-celiac gluten sensitivity, dermatitis herpetiformis, and gluten ataxia. This study evaluated the presence of gluten in oat flours labeled as “gluten-free” marketed in Brazil, using a qualitative immunochromatographic strip test with a detection limit of 5 mg·kg⁻¹. Nine brands of oat flour were analyzed using lateral flow tests, performed in triplicate. The test device is designed to detect gluten in raw materials, finished food products, beverages, and environmental samples. Results showed that two brands tested positive for gluten in all three replicates (22.2% of samples). Two other brands tested positive in only one out of three replicates, which was considered a negative result, totaling 77.8% of samples classified as gluten-free. These findings reveal that, despite “gluten-free” labeling, there is a risk of cross-contamination in some products, which may compromise the safety of individuals with gluten-related disorders. The study emphasizes the need for stricter quality control in the gluten-free food industry and the implementation of more sensitive and standardized methods to detect trace amounts of gluten, thus promoting greater consumer safety and confidence.